Migration and Identity in Nordic Literature - Humpál, Martin; Březinová, Helena (Karolinum Press, 2022)
The book Migration and Identity in Nordic Literature focuses on migration as it has manifested itself in literature and culture in the nineteenth, twentieth and early twenty-first centuries in Denmark, Norway, Sweden, Finland, and Iceland. Since migration almost always leads to a disturbance of identity and creates a potential for conflicts between individuals, as well as between groups of people, the authors have chosen to examine the theme of migration in relation to the questions of identity, both national and individual. The present monograph therefore concentrates on such cases of disturbance, disruption and hybridization of identity, as they are represented in literary works linked to the European North. The book will be of interest to all readers who are interested in issues such as xenophobia, racism, nationalism, cosmopolitism, globalization, cultural transfer, cultural hybridity, multiculturalism and multilingualism.